2021
DOI: 10.2116/analsci.20scp17
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex MicroRNA Detection on a Surface-Functionalized Power-Free Microfluidic Chip

Abstract: Circulating microRNAs (miRNAs) have emerged as promising cancer biomarkers because their concentration profiles in body fluids are associated with the type and clinical stage of cancer. For multiplex miRNA detection, a novel surfacefunctionalized power-free microfluidic chip (SF-PF microchip) has been developed. The inner surface of the SF-PF microchip microchannels was functionalized via electron beam-induced graft polymerization and immobilization of capture probe DNAs. Simultaneous and specific duplex miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previously reported EV detection or isolation methods using microfluidic chips require a pump [ 19 ]. In recent years, we have developed a surface-functionalized power-free (SF-PF) microchip [ 20 , 21 , 22 , 23 , 24 ] prepared by functionalizing the inner surface of the microchannel of a PF microchip using radiation-induced graft polymerization. The SF-PF microchip is an excellent platform for POCT devices because it is convenient to add desired functions without compromising the advantages of the PF microchip.…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported EV detection or isolation methods using microfluidic chips require a pump [ 19 ]. In recent years, we have developed a surface-functionalized power-free (SF-PF) microchip [ 20 , 21 , 22 , 23 , 24 ] prepared by functionalizing the inner surface of the microchannel of a PF microchip using radiation-induced graft polymerization. The SF-PF microchip is an excellent platform for POCT devices because it is convenient to add desired functions without compromising the advantages of the PF microchip.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer biomarkers are a valuable tool for staging certain cancers, monitoring cancer development, and assess the prognosis of treatment [5][6][7]. After the formation of tumor, changes in the levels of several biomarkers can be detected in blood samples or other body fluid samples [8,9]. In order to distinguish subtle changes in levels of biomarkers in complex clinical blood samples or other body fluid samples, therefore, diagnostic analysis must be rapid, sensitive and selective.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the present system enabled the detection of target multiple miRNAs at nanomolar level. Ishihara et al reported multiplex microRNA detection using a new class of microfluidic chip that consisted of polydimethylsiloxane (PDMS) [8]. In sharp contrast to typical ones used for miRNA detection, the present microfluidic chip features a power-free system without the need of an external power source based on the high gas solubility of PDMS [9,10].…”
mentioning
confidence: 99%
“…The inner surface of microchannels can be easily functionalized for the immobilization of capture probe DNAs, which allows the detection of target RNA by hybridization with capture probe in combination with fluorophore-labelled detection probe. The usefulness of such surface-functionalized powerfree (SF-PF) microchip for multiplex detection of cancer biomarkers was demonstrated [8]. They prepared a line-type SF-PF microchip whose inner surface was modified with two kinds of capture probe DNAs for miR-16 and miR-500.…”
mentioning
confidence: 99%